Relevance of a positive latex specific IgE result in a non medical occupational setting - Motsepe, Didintle Christine (Division of Dermatology, 2015)
Background: In 2007, three patients from Impregnated Web Technology (IWT) factory were referred to Groote Schuur occupational clinic with contact dermatitis. The IWT factory manufactures sanding and grinding discs, traditionally a low latex exposure industry. Workers at this factory were introduced to latex gloves in 2004 to protect their hands for various reasons. One of the patient was referred with raised latex specific IgE. Our preliminary diagnosis was irritant contact dermatitis. The dermatitis cleared after avoiding latex gloves. The other two were referred with negative latex specific IgE. One was subsequently diagnosed of fiberglass dermatitis confirmed with histology and the other with urticaria based on the history. Because of the perception that skin problems equate to latex allergy we decided to study the relevance of a positive latex specific IgE in a nonmedical setting. Objective: The objective of this study is to determine the prevalence and relevance of latex sensitization at this traditionally a low latex exposure factory. It also aimed to increase awareness of latex exposure and provide recommendations for preventing and managing latex allergies. Methods: A cross sectional study of the workers on duty was conducted at the IWT factory over 2 days. There were no exclusion criteria. Ethics approval was obtained. Workers who volunteered were asked to sign informed consent and answer 3 questionnaires. Questioned asked were related to glove use at work and at home. They were also examined by the investigator and had a blood sample taken for total IgE and latex specific IgE measurement. Results: There were 160 workers on the factory floor over the study period. Only 81 workers volunteered giving a response rate of 51 %. The point prevalence of latex sensitization was 16 %(13/81). There was a significant relationship between workers who had skin signs and wore glove, however there was no association between glove usage and total and latex specific IgE. A raised latex specific IgE was associated with permanent employment. Conclusion: The prevalence of elevated latex specific IgE amongst workers at IWT factory was high, in the range of that reported of medical personnel, suggesting a source of latex exposure in the work place. The reasons for glove use amongst the workers revealed an appropriate use of natural rubber latex gloves with unnecessary latex exposure. Although we could not link the high prevalence of latex specific IgE to the use of gloves, subgroup analysis with larger numbers of workers may expose an association suggested by a higher prevalence in permanent workers. We suggest the use of more appropriate gloves selected for the protection needed. A latex specific IgE test should be performed only for workers with strong suspicion of latex sensitization, not simply skin signs and symptoms.